2012
DOI: 10.1021/ie301965g
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of the Uranyl Ions on an Amidoxime-Based Polyethylene Nonwoven Fabric Prepared by Preirradiation-Induced Emulsion Graft Polymerization

Abstract: A polyethylene (PE) nonwoven fabric adsorbent with amidoxime (AO) groups denoted as PE-g-PAO is prepared by preirradiation-induced emulsion graft polymerization of acrylonitrile (AN) and subsequent amidoximation of the nitrile groups of the poly(acetonitrile) (PAN) grafting chains with hydroxylamine (NH2OH). The chemical structure, thermal stability, and mechanical intensity are evaluated by means of Fourier transform infrared, thermogravimetric analysis, differential scanning calorimetry, and tensile tests, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 35 publications
2
61
0
Order By: Relevance
“…The related thermodynamic parameters calculated from the temperature-dependent isotherms are listed in Table 4. The positive values of standard enthalpy changes (∆H 0 ) indicated an endothermic process for the adsorption of UO 2 2+ on 2.0PAO/rGO composite that was consistent with our observed results and the literature [15,16,36]. The negative values of Gibbs free energy change (∆G 0 ) indicated that UO 2 2+ adsorption on 2.0PAO/ rGO was a spontaneous process [37].…”
Section: +supporting
confidence: 91%
See 1 more Smart Citation
“…The related thermodynamic parameters calculated from the temperature-dependent isotherms are listed in Table 4. The positive values of standard enthalpy changes (∆H 0 ) indicated an endothermic process for the adsorption of UO 2 2+ on 2.0PAO/rGO composite that was consistent with our observed results and the literature [15,16,36]. The negative values of Gibbs free energy change (∆G 0 ) indicated that UO 2 2+ adsorption on 2.0PAO/ rGO was a spontaneous process [37].…”
Section: +supporting
confidence: 91%
“…Therefore, the introduction of proper functional groups onto GO surfaces is crucial for its real application in the high extraction of UO 2 2+ from seawater. Owing to its excellent affinity with UO 2 2+ , amidoxime (AO) was widely accepted as one of the most promising binding sites for UO 2 2+ due to its specific binding affinity with UO 2 2+ [15][16][17][18]. For this reason, modification of the GO surface with AO would thought to result in the high extraction of UO 2 2+ from seawater.…”
Section: Introductionmentioning
confidence: 99%
“…Sorption amount q e (mg g À1 ) and distribution coefficient K d (mL g À1 ) of either uranium(VI) or other metal ions were calculated according to the following formulae [30][31][32].…”
Section: Batch Sorption Experimentsmentioning
confidence: 99%
“…2. It was clear that the peaks at 927 cm -1 and 1647 cm -1 of AO/CMK-3 were corresponded to stretching vibration of -C=N-bond and -N-O-bond respectively, and the peak at 2940 cm -1 was attributed to symmetrical stretching vibration of C-H bond [34].…”
Section: Results and Discussion Characterizationmentioning
confidence: 99%